Double-Layered Circular Advancement Flap for Reconstruction of Inguinal Defects - Arpaci, Enver; Altun, Serdar (Wolters Kluwer Medknow Publications, 2017)
Objective: Vascular graft infections are rare complications but can lead to life-threatening outcomes for the patient. Conventional treatment methods are the removal of the vascular graft and an extra-anatomic by-pass procedure. Unfortunately, this treatment presents high morbidity and mortality rates. Treatment of the deep-level perivascular synthetic graft infection and closure of exposed vascular graft reduce graft infection, thereby help to reduce mortality and morbidity rates. Material and Methods: Between 2009-2013 seven cases of complicated defect that involved perivascular graft infection in the inguinal region were performed using omega advancement flaps. In this technique, a circular-shaped flap with a diameter corresponding to the defect was planned adjacent to the defect after debridement of the infected perivascular and the necrotic skin areas. To facilitate the advancement of the flap and to support the subcutaneous region, deepithelialized equilateral triangular flaps were designed on both sides of the main circular flap. Results: Wound dehiscence and infection recurrence did not occur in the follow-up period. No secondary surgeries were required to change the segment of the vascular graft. All flaps survived without any complications such as hematoma, flap necrosis or infection. The results were satisfactory both aesthetically and functionally. Conclusion: Omega fasciocutaneous advancement flap is a reliable, suitable and easy method for the reconstruction of complex inguinal vascular infections.
Inguinal bölge rekonstrüksiyonunda iki katmanli sirküler ilerletme flebi
Keywords: Synthetic vascular graft; inguinal defect; infection; advancement flap